Current problems of legal regulation of democratic practice (fundamentals of the concept of the Code of Democracy) - A.V. Pogodin; E.V. Krasnov; A.V. Putintsev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The structure of legal regulation of democratic practice was analyzed. General normative legal regulation, during which the federal legislator and society, through the institution of referendum, develop a system of norms and form a normative legal model of democratic practice, was singled out. The organizational and legal activities of the subjects of democratic practice were described. Legal self-regulation and individual normative legal regulation of democratic practice were considered. Legal conflicts and their regulation were covered in detail. The importance of monitoring of law translation into social life and interpretation of law was emphasized. It was shown that the important public and state role played by democratic practice explains the necessity to consolidate the regulatory norms in the form of a Code of Democracy. The theoretical basis for the concept of the Code of Democracy was proposed. It was suggested that the theoretical basis should include the fundamental problems of practice reflecting the patterns of its functioning and development. In particular, the practice-forming, practice-destroying, and practice-promoting elements of democracy were analyzed. A classification of practice-forming phenomena, relations, and processes that are parts of the general legal regulation of democratic practice was provided.